Answer:
f(g(x)) = x² - 5x +4
Step-by-step explanation:
<u><em>Explanation</em></u>
Given that the functions
f(x) = x² + 3 x and g(x) = x-4
f(g(x)) = f(x -4) (∵ g(x) = x-4)
= (x-4)² + 3(x-4)
= x² - 2(4)x + 4² + 3x -12
= x² - 8 x + 16 + 3x -12
= x² - 5x +4
∴ f(g(x)) = x² - 5x +4
Answer:
<AFB
Step-by-step explanation:
Supplementary angles are the angles that's sum up to 180° which is called a straight angle.
In this question we see AFB is supplementary to DFA for DFB is the straight angle.
Answer:
Yes
Step-by-step explanation:
It is a first-degree equation. Look at the exponents of each variable (x, y), they are not written because they are 1
Hope this helps
Answer:
a picture would help
Step-by-step explanation:
you need a picture to further understand and answer the question right